Modeling Hawaiian Agroecology: Depicting traditional adaptation to the world's most diverse environment - Lincoln, Noa Kekuewa; Haensel, Thomas P.; Lee, Tiffany M. (Frontiers in Sustainable Food Systems, 2023)
Most neglected and underutilized crops were developed and utilized within indigenous agroecological cropping systems. While crop suitability must consider the constraints of the environment, the conditions of agroecological systems and the role of crops within those systems should be considered. Such consideration may guide the implementation of appropriate farming systems specific to different ecosystems and microhabitats. Using the Hawaiian archipelago as a model system of socioecological dynamics, we consider the distribution of agroecological systems and their associated crops to explore how agroecological suitability changes across climate, topography, and soils. We conduct spatial modeling of the potential nature and extent of seven agroecological archetypes based on historical records. The seven spatial models of pre-colonial agroecological systems produced extents distributed across much of the Hawaiian archipelago, with clear adaptive patterns within and across the islands. The distribution of cropping system further affects the appropriateness of crop species application. We argue that the consideration of agroecological niches and associated cropping systems is critical for realizing the potential of underutilized crops and improving the efficiency of contemporary agricultural systems.